2014
DOI: 10.1186/1472-6874-14-38
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical activity and body mass index on menopausal symptoms in Turkish women: a cross-sectional study in primary care

Abstract: BackgroundConsidering the fact that, due to recent evidence, many women no longer prefer hormone replacement therapy, it is especially important to develop intervention options to alleviate menopausal symptoms. Although there is conflicting evidence concerning effectiveness, there is an indication that physical activity and weight control may be useful for alleviating symptoms. The aim of this study was to investigate the effect of physical activity and body mass index on menopausal symptoms among menopausal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 42 publications
4
37
1
9
Order By: Relevance
“…We found that women with a normal BMI had a significantly lower total MRS score compared with underweight, overweight or obese women and this is consistent with another previous study (26). The association between obesity and vasomotor symptoms is contradictory.…”
Section: Discussionsupporting
confidence: 81%
“…We found that women with a normal BMI had a significantly lower total MRS score compared with underweight, overweight or obese women and this is consistent with another previous study (26). The association between obesity and vasomotor symptoms is contradictory.…”
Section: Discussionsupporting
confidence: 81%
“…The body fat when higher is also a source of reproductive hormones thus interfering with the physiology of menopause. Postmenopausal symptoms in Turkish women were studied by Tan MN et al 9 In their study 305 women between ages 45 to 60 were recruited. They found though very contrary results by reporting BMI was not associated with total menopausal symptoms and the subscales, excluding depressive mood (p=0.009).…”
Section: Relation Of Average Age Of Menopause With Bmimentioning
confidence: 99%
“…12 Estudos mostram que a sintomatologia climatérica apresenta-se menos intensa entre as mulheres fisicamente ativas, quando comparadas às menos ativas e/ou sedentárias. 13,14 Tairova e De Lorenzi 15 mostraram em seu estudo que as mulheres de meia-idade, fisicamente ativas, apresentaram maior qualidade de vida nos domínios somato-vegetativos, urogenitais e psicológicos, quando comparados às mulheres sedentárias. Pesquisa de base populacional no nordeste brasileiro também mostrou que as mulheres climatéricas com maior nível de atividade física tinham maiores escores de qualidade de vida em comparação com as mulheres sedentárias.…”
Section: Introductionunclassified
“…[13][14][15]22 As mulheres praticantes de exercícios físicos, em nosso estudo, apresentaram menos sintomas somáti-cos e vasomotores que as mulheres não praticantes. A esse respeito, pesquisas têm mostrado resultados semelhantes, visto que mulheres com prática regular de exercícios físicos manifestaram menor intensidade de sintomas somáticos, alívio nas ondas de calor e fogachos, melhora do humor e da depressão.…”
unclassified